A Semantic Analysis on Some Selected Songs of Beautiful Nubia - Oyelami, Oluwabukunmi Hannah (New Trends in Psychology, 2025)
This study delves into the lyrical world of Beautiful Nubia, a renowned Nigerian musician, by conducting a semantic analysis of three of his songs: “Ikoko Akufo,” “Moworesire,” and “Seven Lives” through a qualitative approach, this research uncovers the underlying meanings, themes, and messages embedded in the songs. The analysis reveals that Beautiful Nubia’s lyrics traverse themes of social justice, personal growth, love, and existential introspection. The study employs semantic tools to dissect the language, metaphorical expressions, and poetic devices employed by the artist, exposing the depth and richness of his lyrics. The findings offer insights into the artist’s worldview, cultural influences, and the cultural significance of his music. This research contributes to the understanding of African music’s role in reflecting and shaping societal values and beliefs.